2022
DOI: 10.3390/plants11070913
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Auxin (Indole-3-butyric Acid) on Adventitious Root Formation in Peach-Based Prunus Rootstocks

Abstract: Several Prunus species are among the most important cultivated stone fruits in the Mediterranean region, and there is an urgent need to obtain rootstocks with specific adaptations to challenging environmental conditions. The development of adventitious roots (ARs) is an evolutionary mechanism of high relevance for stress tolerance, which has led to the development of environmentally resilient plants. As a first step towards understanding the genetic determinants involved in AR formation in Prunus sp., we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…This increase was not significantly different from the IBAP treatment, suggesting a similar overall enhancement of biomass. These findings collectively demonstrate that XOS effectively promotes the biomass and elongation of adventitious and lateral roots in lettuce, paralleling the effects observed with the exogenous application of IBAP [30].…”
Section: Xylooligosaccharides Promote Lettuce Root Growthsupporting
confidence: 70%
See 1 more Smart Citation
“…This increase was not significantly different from the IBAP treatment, suggesting a similar overall enhancement of biomass. These findings collectively demonstrate that XOS effectively promotes the biomass and elongation of adventitious and lateral roots in lettuce, paralleling the effects observed with the exogenous application of IBAP [30].…”
Section: Xylooligosaccharides Promote Lettuce Root Growthsupporting
confidence: 70%
“…Notably, shoot dry weight also increased significantly by 26.7 under XOS treatment compared to WT (Figure 3). This increase was not significantly ferent from the IBAP treatment, suggesting a similar overall enhancement of biom These findings collectively demonstrate that XOS effectively promotes the biomass elongation of adventitious and lateral roots in lettuce, paralleling the effects observed w the exogenous application of IBAP [30]. Distinct lowercase letters denote significant differences among treatments at the 0.05 significa level.…”
Section: Xylooligosaccharides Promote Lettuce Root Growthsupporting
confidence: 53%
“…The quality of a rooted cutting is considered based on the morphological characteristics of the aerial parts and adventitious roots, which will determine their vigor, health, uniformity, and plant fast establishment [4,5]. Their capacity can vary greatly according to the following factors: the species [6], the carbohydrate content of the cutting [7], the rooting environment [8], the level of endogenous phytohormones such as auxins [9,10] and the application of biostimulators [11]. Indole-3-butyric acid (IBA) has been identified as an auxin precursor, therefore as an endogenous constituent in several plants that is converted to 3-indoleacetic acid (IAA), the main hormone of the auxins group, in a peroxisomal β-oxidation process [12].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the current study, the effects of genotype on the rooting potential of cuttings have been observed in other members of the Rosaceae family, such as a broad spectrum of wild Prunus germplasm, where cuttings from different wild genotypes presented dramatic differences in rooting capacity, ranging in some cases from 0 to >50% rooting of different genotypes under matching treatments within each tested Prunus species as well as between different wild species of the genus Prunus [48]. Additional studies reported significant effects of genotype on the rooting of cuttings of Prunus rootstock germplasm tested both under mist and hydroponically [49][50][51]. Further studies on Rosaceae small trees have reported noteworthy differences in rooting of cuttings between wild genotypes of Rosa canina L. but also between wild genotypes of damask roses (R. × damascena Herrm.)…”
Section: Asexual Propagation Of Greek Native Amelanchier Ovalismentioning
confidence: 99%